PERENCANAAN DAN PEMBUATAN SIMULATOR RELE ARUS LEBIH ELEKTRONIK BERBASIS MICROCONTROLLER - Hunaini, Fachrudin; Rihi, Enos Kopa; Mukhsim, Mohammad; Effendy, Dedi Usman (JASEE Journal of Application and Science on Electrical Engineering, 2024)
Electrical power distribution has risks that cannot be avoided, namely short circuit disturbances, both symmetrical and asymmetrical, temporary or permanent. Electricity providers' efforts to avoid or localize disturbances use protection systems, one of which is the Over Current Relay (OCR). The use of OCR in electric power transmission or distribution networks requires careful current and time settings according to the characteristics of the fault and the location of the fault. As an effort to facilitate operators and academics in the process of understanding and providing learning media or training to be able to simulate the current and time settings of OCR in securing the electric power transmission/distribution network, an OCR setting simulator of the electric power transmission or distribution network system is needed. built electronically using a microcontroller. The simulator built represents a three-phase electrical network with treatment of single-phase, inter-phase and three-phase faults. In each type of short circuit treatment, the fault current that occurs in section I (upstream) is greater than the fault current that occurs downstream, namely section II and section III. The working time of the relay in each section is faster at greater fault current values ​​which are influenced by the variable TMS (Time Multiple Setting) and setting current (IS) values